Analisis Penggunaan Dompet Digital, Sikap Keuangan dan Gaya Hidup Terhadap Perilaku Konsumtif Karyawan PT Chang Shin Indonesia Karawang - Berliana Ananda Kutaningtyas; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The development of digital technology has driven changes in the payment system and consumption patterns of society, including among employees in the manufacturing industry. This study aims to analyze the influence of the use of digital wallets, financial attitudes, and lifestyles on the consumtive behavior of employees of PT Chang Shin Indonesia Karawang. The method used is associative quantitative research with a purposive sampling technique of 100 respondents. Data were collected through a questionnaire with a Likert scale and analyzed using multiple linear regression tests with the help of SPSS 30 software. The results of the study indicate that the variables of digital wallets and financial attitudes do not have a significant effect on consumtive behavior. Meanwhile, the lifestyle variable has a significant effect on consumtive behavior. Simultaneously, the three independent variables have a significant effect on consumtive behavior. The implications of this study indicate that it is necessary to increase financial literacy and awareness of lifestyle management to avoid excessive consumtive behavior.